Real-world effectiveness of tofacitinib in monotherapy or in combination with csDMARDs in patients with rheumatoid arthritis: A collaboration between Dutch registries (TOFADUDAP study) - Isabell S. Nevins; Herman Kasper Glas; Floor Reimann; Reinhard Bos; Marieke P. D. de Buck; K. Wiepke Drossaers-Bakker; Mirjam C. Hegeman; Tom W. J. Huizinga; Sytske Anne Bergstra (Clinical Rheumatology, 2026)
Abstract Objective To compare real-world effectiveness of tofacitinib monotherapy to adalimumab monotherapy, and tofacitinib and adalimumab in combination with csDMARDs in Rheumatoid Arthritis (RA) subgroups. Methods Retrospective routine care data was used from six Dutch cohorts for RA patients who initiated tofacitinib or adalimumab between 2001 and 2022. Drug survival of tofacitinib monotherapy ( n = 229) was compared with that of tofacitinib combination-therapy ( n = 179), adalimumab monotherapy ( n = 1019) and adalimumab combination-therapy ( n = 1361) using Kaplan–Meier curves and Cox regression. Drug survival was evaluated as an indirect measure of treatment persistence. Exploratory analyses assessed effect modifications by anti-citrullinated protein antibody (ACPA) status and age at treatment onset in both models. Results Patients who started tofacitinib monotherapy were older compared to other treatment groups (61 vs 55, 58 and 58 years) and had used at least one previous b/tsDMARD more often compared to the adalimumab treatment groups (36% vs 41%, 19% and 13%). Compared to tofacitinib monotherapy, the risk of drug discontinuation was similar for tofacitinib combination-therapy (aHR 1.22, 95% CI: 0.96–1.54) and adalimumab monotherapy (aHR 0.89, 95% CI: 0.73–1.09) but lower for adalimumab combination-therapy (aHR 0.78, 95% CI: 0.63–0.96). Older age was associated with significantly higher risk of drug discontinuation. No effect modification by ACPA was observed. Conclusion Based on real-world data from six Dutch cohorts, drug discontinuation was higher for tofacitinib than for adalimumab, with similar outcomes with or without csDMARDs. Older age was associated with a higher risk of drug discontinuation independently of treatment group, although this finding may be influenced by factors beyond treatment effectiveness. Key Points • In a real-world setting tofacitinib was observed to have similar drug survival in mono- and combination therapy • ACPA status did not influence drug survival • Older age was related to a higher risk of drug discontinuation independently of treatment